Amalan membuat keputusan dalam kalangan pentadbir sekolah menengah - Yacob, Norsurayahani (2012)
The purpose of this is to identify the external and internal factors influencing decision-making process among administrators of secondary school in Segamat District. The respondents were comprised of 74 male and female administrators from 24 secondary schools. The data was collected using questionnaire validated by lecturer from UTM. The Alpha Cronbach validity for the instrument used in this research is 0.953. The data in this research was analysed using Statistical Package for Social Science (SPSS) 17.0 in the formed of descriptive statistics such as frequency, percentage, mean and standard deviation, and also the inferential statistics using the t-test. Result obtained shown that the external factors influencing decision-making process among administrators are interpersonal relationship, habit and culture in organization, and information system and communication. Meanwhile, the internal factors influencing decision-making process among administrators are knowledge and skills, individual value and concept, decision-making style and intuition, and personality and traits. The finding indicates that there is no significant difference between male and female in term of external factors among the respondents. Meanwhile, the finding also indicates there are significant differences between male and female in term of internal factors among the respondents. Result obtained shown that the administrators follow the systematic steps in decision-making process based on certain method frequently.